Exploring the relationships between learning styles, online participation, learning achievement and course satisfaction: An empirical study of a blended learning course. (22nd December 2014) - Cheng, Gary; Chau, Juliana
Abstract: The purpose of this study was twofold: first, to explore the relationship between students' learning styles and their online participation in a blended learning course, and second, to investigate the relationships of students' online participation with their learning achievement and with course satisfaction. A total of 78 undergraduate students from a general education course called Digital Citizenship took part in the study. All the participants were required to participate in four different types of online activity: information access, interactive learning, networked learning and materials development . The study used the method of partial least squares to explore the relationships between different constructs. The results indicate that students' learning styles were significantly related to online participation and that online participation in networked learning and materials development was significantly related to their learning achievement and course satisfaction. This study highlights not only the crucial role of learning styles in online participation but also the importance of individual constructivism and social interaction for effective online learning.